Mechanical behaviour of sugar maple in cantilever bending under constant and variable relative humidity conditions. (November 2013) - Segovia, F; Blanchet, P; Laghdir, A; Cloutier, A
Abstract : The mechanical behaviour of wood over time depends on temperature, relative humidity, applied load and the direction of the applied load, among other factors. In the present study, the mechanical behaviour of sugar maple ( Acer saccharum Marsh.) wood was determined using creep tests in cantilever bending. These tests were carried out at different load levels, in a controlled environment chamber at a constant temperature of 30± 0·5°C and a relative humidity of 37, 67 and 83% for constant conditions and a relative humidity ranging from 37 to 83% for variable conditions. The specimens were oriented in a radial pattern and cut to 110 mm in length, 25 mm in width and 7 mm in thickness. The results show the impact of load levels and moisture content. Under constant conditions, the results show a linear behaviour of viscoelastic creep. Under variable relative humidity conditions, changing moisture contents resulted in significantly higher creep (mechanosorptive) compared to constant conditions.